New distribution record of Hipposideros grandis G.M. Allen, 1936, Grand Leaf-nosed Bat (Chiroptera, Hipposideridae), from Bangladesh based on morphometric and molecular evidence - Md. Kamrul Hasan; Ashis Kumar Datta; Anik Saha; Sajeda Begum (Check List)
We confirm the presence of Hipposideros grandis G.M. Allen, 1936 from Baraiyadhala National Park, Bangladesh. The identification was based on morphometric attributes of two captured individuals and sequencing of the mtDNA cytochrome oxidase subunit I (COI) gene. The roosting habitat was chiefly degraded mixed evergreen forests characterized by steep and undulating terrain with many waterfalls and hilly streams. Our new record in Bangladesh extends the westernmost known range of H. grandis. The ecology of this bat species should be studied, as very little is known about it.